Supplementation of spirulina (Spirulina platensis) on yolk colour, egg quality and production performance of laying hens (Bangladesh Veterinarian, 2018)
A total of 96 Shaver 579 laying hens of 78 weeks of age were studied for the effects on egg production of dietary supplementation with spirulina (Spirulina platensis). The hens were divided into four dietary treatments with six replications of four birds in each group. Birds of three groups were supplemented with 0.1%, 0.2% and 0.3% spirulina and one group was kept as control. Yolk colour significantly improved (P